Safety of Sarilumab in the treatment of rheumatoid arthritis: a real-world study based on the FAERS database - Wang, Dahui; Guo, Qian; Chen, Xin; He, Jinguang; Deng, Jiehua (Frontiers in Medicine, 2025)
BackgroundRheumatoid Arthritis (RA) is a chronic autoimmune disease causing joint pain, swelling, and systemic symptoms like fatigue, with higher incidence in females and increased risk with age. It often co-exists with depression, imposing a significant global health burden with high annual cases and substantial economic losses. Sarilumab, a fully humanized IgG1 monoclonal antibody targeting the IL-6 receptor α, has shown efficacy in clinical trials but requires real-world safety monitoring.MethodsThis study analyzed Sarilumab-related adverse drug event (ADE) reports from the FAERS database (Q2 2017–Q1 2025). Data were cleaned and analyzed using SAS 9.4, with signal detection via Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multivariate Gamma-Poisson Shrinker (MGPS).ResultsA total of 14,940 Sarilumab users with 42,730 adverse events (AEs) were included. AE signals were detected across all 26 System Organ Classes (SOC), with the highest in Infections and Infestations (62 signals), General Disorders and Administration Site Conditions (44), Musculoskeletal and Connective Tissue Disorders (36), and Surgical and Medical Procedures (36). Nearly half of AEs occurred within 30 days (49.56%), and 15.79% after 360 days. Common AEs included pain, joint swelling, and injection site reactions, while severe reactions included serious infections and anaphylaxis. Some AEs not listed on the drug label, such as fatigue and alopecia, were also identified.ConclusionThis real-world analysis highlights Sarilumab’s safety profile, emphasizing the need for close patient monitoring, particularly during the early initiation phase and throughout long-term treatment. The findings provide valuable insights for clinicians in pre-medication assessment, during-treatment monitoring, and adverse reaction management, while underscoring the need for further research into the mechanisms and risk factors of these adverse events.